A Stereocontrolled Total Synthesis of Lipoxin B4 and its Biological Activity as a Pro‐Resolving Lipid Mediator of Neuroinflammation. Issue 35 (19th May 2022) - Frank Lee, C.; Brown, Carla E.; Nielsen, Alexander J.; Kim, Changmo; Livne‐Bar, Izhar; Parsons, Philip J.; Boldron, Christophe; Autelitano, François; Weaver, Donald F.; Sivak, Jeremy M.; Reed, Mark A.
Abstract: Two stereocontrolled, efficient, and modular syntheses of eicosanoid lipoxin B4 (LXB4 ) are reported. One features a stereoselective reduction followed by an asymmetric epoxidation sequence to set the vicinal diol stereocentres. The dienyne was installed via a one‐pot Wittig olefination and base‐mediated epoxide ring opening cascade. The other approach installed the diol through an asymmetric dihydroxylation reaction followed by a Horner‐Wadsworth‐Emmons olefination to afford the common dienyne intermediate. Finally, a Sonogashira coupling and an alkyne hydrosilylation/proto‐desilylation protocol furnished LXB4 in 25 % overall yield in just 10 steps. For the first time, LXB4 has been fully characterized spectroscopically with its structure confirmed as previously reported. We have demonstrated that the synthesized LXB4 showed similar biological activity to commercial sources in a cellular neuroprotection model. This synthetic route can be employed to synthesize large quantities of LXB4, enable synthesis of new analogs, and chemical probes for receptor and pathway characterization. Abstract : Two stereocontrolled, efficient, and modular syntheses of eicosanoid lipoxin B4 (LXB4 ) are reported along with full spectral characterization of the natural product for the first time. Synthetic LXB4 exhibited significant neuroprotection in a cellular model of retinal ganglion cell survival assay. Our synthetic routes enable syntheses of new analogs and chemical probes for receptor and pathway identification.